1 day SiH lenses: A good choice for my patients?. Issue 11 (November 2020) - Dumbleton, Kathy; Sulley, Anna
Abstract : Dr Kathy Dumbleton and Anna Sulley summarise the key points from a recent peer-reviewed paper summarising the evidence of the published literature that supports the benefits of both a 1 day modality and silicone hydrogel materials from patient needs to clinical performance, health outcomes and compliance, and highlights the advantages that can be provided to both new and existing contact lens wearers. (C76679, one distance learning point suitable for optometrists, contact lens opticians and dispensing opticians)